Combined radiological-endoscopic management of difficult bile duct stones: 18-year single center experience. (November 2015) - Cannavale, Alessandro; Bezzi, Mario; Cereatti, Fabrizio; Lucatelli, Pierleone; Fanello, Gianfranco; Salvatori, Filippo Maria; Fanelli, Fabrizio; Fiocca, Fausto; Donatelli, Gianfranco
Objectives: Clinical evidence regarding radiological–endoscopic management of intrahepatic bile duct stones is currently lacking. Our aim is to report our 18-year experience in combined radiological–endoscopic management of intrahepatic difficult bile duct stones. Methods: From June 1994 to June 2012, 299 symptomatic patients with difficult bile duct stones were admitted to our institution. Percutaneous transhepatic cholangiography (PTC)/biliary drainage/s was performed, dilating the PTC track to 10 or 16 French within 3–7 days. Afterward we carried out percutaneous transhepatic cholangioscopy (PTCS) with electrohydraulic lithotripsy (EHL) and/or interventional radiology techniques. Follow up was made with clinical/laboratory tests and ultrasound (US). We retrospectively analyzed our radiological–endoscopic approach and reported our technical and clinical outcomes. Results: Complete stone clearance was achieved in 298 patients after a maximum of 4 consecutive sessions. Most patients (64.6%) were treated with PTCS/EHL alone, while the remaining with radiological techniques alone (26%) or a combination of both techniques (13.3%). Recurrence of stones occurred in 45 cases (15%, Tsunoda class III and class IV) within 2 years and were successfully retreated. Major adverse events were: 5 (1.6%) cases of massive bleeding that required embolisation, 2 (0.66%) perforations of the common bile duct and 31 cases (10.3%) of acute cholangitis managed with medical therapy or intervention. Conclusion: After 18 years of experience we demonstrated that our combined radiological–endoscopic approach to 'difficult bile duct stones' may result in both immediate and long-term clearance of stones with a low rate of adverse events.